What can we learn about systems leadership from the building of a Welsh surge hospital and how might this be applied beyond the current COVID-19 response?. Issue 2 (24th December 2020) - Beharrell, William; Richards, Len; Driscoll, Martin; Gray, Jonathon
Abstract : Background: Methods: It draws on a series of 20 interviews with key protagonists and employs a Bakhtinian approach to narrative analysis, which explores the interplay between individual accounts and larger sociocultural themes. Results: Conclusions: It concludes that the success in managing the complexity of this project can largely be attributed to a systems leader approach that draws on the power of an agile network to be replenished and redeployed against rapidly evolving strategic objectives. This effectively constitutes a parallel operating structure, which is devoted to the design and implementation of strategy based on a continual assessment of the organisation and serves to strengthen rather than supersede established hierarchical structures of authority.